Geographic remoteness and socioeconomic disadvantage reduce the supportiveness of food and physical activity environments in Australia - Morgan Darcy; Joy Parkinson; Nicole McDonald; Stephanie Moriarty; Shanti Kadariya; Diksha Sapkota (Elsevier, 2022)
Abstract Objective: An analysis of food and physical activity environments in relation to socioeconomic disadvantage was conducted in 25 communities across Queensland, Australia. Methods: Physical activity and food environments were assessed in 25 Queensland communities using The Systematic Pedestrian and Cycling Environmental Scan (SPACES) and the Nutrition Environment Measurement Survey (NEMS). Spearman's correlation tested the association between physical activity and food environments and degree of remoteness and socioeconomic disadvantage of each region. Results: A significant negative association was observed between the supermarket food environment and degree of remoteness and socioeconomic disadvantage. All regions have a moderately supportive environment for physical activity. Food availability and price varied in supermarkets with more remote communities having less supportive food environments. Conclusions: Areas with a high degree of remoteness and socioeconomic disadvantage were more likely to experience disadvantages in the physical activity, supermarket, and restaurant food environments than metropolitan areas and socioeconomically disadvantaged areas. Implications for public health: Socioeconomic disadvantage and remoteness were associated with reduced supportiveness of the built environment hindering the ability of consumers to make healthy food and physical activity choices. Improving the food and physical activity environments in these areas may assist in reducing the health inequalities experienced by these communities.